2017
DOI: 10.1148/radiol.2016160646
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted Imaging as a Treatment Response Biomarker for Evaluating Bone Metastases in Prostate Cancer: A Pilot Study

Abstract: Purpose To determine the usefulness of whole-body diffusion-weighted imaging (DWI) to assess the response of bone metastases to treatment in patients with metastatic castration-resistant prostate cancer (mCRPC). Materials and Methods A phase II prospective clinical trial of the poly-(adenosine diphosphate-ribose) polymerase inhibitor olaparib in mCRPC included a prospective magnetic resonance (MR) imaging substudy; the study was approved by the institutional research board, and written informed consent was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 25 publications
7
71
0
Order By: Relevance
“…The use of ADC for therapeutic assessment of bone metastases has also been investigated because current response evaluation criteria like RECIST are of limited utility for bone metastasis. Consistently, studies have revealed an increase in ADC after therapy . This is thought to reflect greater water diffusivity from tumor cell death.…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 55%
See 4 more Smart Citations
“…The use of ADC for therapeutic assessment of bone metastases has also been investigated because current response evaluation criteria like RECIST are of limited utility for bone metastasis. Consistently, studies have revealed an increase in ADC after therapy . This is thought to reflect greater water diffusivity from tumor cell death.…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 55%
“…This is thought to reflect greater water diffusivity from tumor cell death. Because they are common and of clinical concern, metastases from prostate cancer were used in the majority of the studies . Sclerotic bone lesions may lower the sensitivity of DWI due to their low water content, although one study of sclerotic bone metastases showed no association between computed tomography (CT) radiodensity and mean ADC .…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 99%
See 3 more Smart Citations